Students’ Perceptions on a Good Tertiary Foreign Language Teacher - Siti Tarwiyah (Register Journal, 2013)
This paper investigates students’ perception of tertiary teachers’ attitude, method of teaching and classroom management in the teaching and learning of (professional, pedagogic, social and personality competence) English and Arabic Language at IAIN Walisongo Semarang. This study is designed quantitavely and qualitatively using closed and open-ended questionnaire for collecting data. The subject of this research is the second semester students of the two faculties at IAIN Walisongo who, in that semester, take Arabic or English language course. The subject is chosen because based on 2012 course distribution, English and Arabic are distributed in the first and the second semester. The findings revealed that it is clearly seen that KPI (Islamic Communication Broadcasting) department students have better perception to their English language teachers. Meanwhile, students who have better perception to their Arabic Language Teachers are those from Islamic Counseling Departments (BPI) of Dakwah faculty. Data of Tarbiyah Faculty shows Arabic language teachers are dominating. Arabic language teachers win 0.5 over English language teachers in almost all characteristics. This implies that expected performance of students in English Language is based on the teachers’ attitude, method of teaching the subject and classroom management. Based on the above-findings, recommendations were made.Keywords:Perception ; Tertiary Teachers ; Personality Social and Pedagogic Competence;  English Language;  Teaching/Learning